Fiscal federalism in the Baltic countries - Viktor Trasberg (European Regional Science Association (ERSA), 2002)
In the democratic societies local government handles many functions typical of the welfare states. The relationships between central government and local municipalities are complex and concern very many different, particularly socially sensitive aspects. In the Baltic countries new institutions and economic infrastructure are being created to establish the foundations for a pluralist and democratic society. Extensive political and fiscal decentralization of local governments is now under way in all these states as a reaction to the overcentralization during the Soviet past. The presentation concentrates on analyses and comparisons of different fiscal decentralization issues on the Baltic countries. The main objectives of the study are: - design of fiscal systems and intergovernmental fiscal relations - profile of sub-national revenues and expenditures - analyses of match between local expenditures and the corresponding revenues - reginal fiscal disparities reasons Today main problems in all three Baltic countries is that local governments have very limited resources to fulfil their main functions - provide variety of public services like education and social care. Their financial resources and administrative capacity are often limited and strongly controlled by the central authorities. In addition, municipalities revenue basis varies extremely by different regions within the countries. As a result, living standard disparities among municipalities are incredibly large and continue to grow. Differences in public services and incomes eventually follow to discarded migration flows, excessive population concentration in the capital city regions (especially in Latvia and Estonia). The most important goal of the fiscal reforms is to enhance the administrative capacity of different level of governments, democratization of the decision making process and giving public spending programs required transparency. Therefore, the fiscal functions and roles of the central and local governments in the Baltic countries need theoretical explanation as well empirical analyses.
Keywords: 330